Perancangan E-commerce Website Berbasis Search Engine Optimization (SEO) untuk Optimalisasi Manajemen Pemasaran Pusat Penjualan Kapal Perikanan di Daerah Jawa Tengah - Caniago, Fahlan Parezki; Rindo, Good; Manik, Parlindungan; Satoto, Sapto Wiratno (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Negeri Batam, 2024)
The advancement of technology in the modern era greatly supports the business world in improving quality and customer service. Websites, as a form of technological development, serve as significant tools for information and promotion, directly influencing a company's success. The capture fisheries sector, particularly the wooden shipbuilding industry, also needs to adopt such technological advancements due to the crucial role of digital transformation in today's buying and selling processes. This research focuses on developing an e-commerce website utilizing Search Engine Optimization (SEO) to optimize marketing management for fishing boat sales in Central Java. The goal is to establish the website as an alternative platform for marketing fishing boats, providing benefits as a promotional medium and simplifying the buying and selling process. The Hub marketing method is used in designing the website with an e-marketplace interface. The study concludes that this website can serve as an effective and efficient alternative in the fishing boat trading business, with successful SEO implementation.